YouTube as a source of information on thoracic outlet syndrome: quality and reliability analysis - Yurttutmuş Tatlı, Zeynep Rukiye; Ferahman, Demet (The European Research Journal, 2025)
Objective: This study aimed to evaluate the quality, reliability, and characteristics of the most-viewed YouTube videos on thoracic outlet syndrome and to identify differences in quality based on content and source. Methods: A systematic search was conducted on YouTube using four keywords related to thoracic outlet syndrome. A total of 200 videos were initially selected, of which 75 met the inclusion criteria after excluding duplicates, non-English videos, off-topic content, and videos under one minute. Video characteristics, including views, likes, duration, content type, and source, were recorded. Reliability and quality were assessed using the modified DISCERN scale, Journal of the American Medical Association benchmark criteria, and the Global Quality Scale. Results: Among the analyzed videos, 46.7% were uploaded by non-physician health workers, 40% by physicians, and 13.3% by independent users. Disease-specific information constituted 50.7% of the content, while 20% focused on exercises, 17.3% on conservative management, and smaller percentages on patient experiences and surgical techniques. The median scores were modified DISCERN: 3.0, Journal of the American Medical Association benchmark criteria: 2.0, and Global Quality Scale: 3.0. Only 29.3% of the videos were categorized as high-quality, while the majority were of medium or low quality. All high-quality videos were found to have modified DISCERN>3. Positive correlations were identified between modified DISCERN, Journal of the American Medical Association benchmark criteria, and Global Quality Scale scores (P